2006
DOI: 10.4049/jimmunol.176.9.5338
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Functional Virus-Specific Memory CD8+ T Lymphocytes in Vaccinated, Simian Human Immunodeficiency Virus-Infected Rhesus Monkeys

Abstract: Functional impairment of virus-specific memory CD8+ T lymphocytes has been associated with clinical disease progression following HIV, SIV, and simian human immunodeficiency virus infection. These lymphocytes have a reduced capacity to produce antiviral cytokines and mediators involved in the lysis of virally infected cells. In the present study, we used polychromatic flow cytometry to assess the frequency and functional capacity of central memory (CD28+CD95+) and effector memory (CD28−CD95+) subpopulations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 38 publications
1
27
0
2
Order By: Relevance
“…It was demonstrated that i.m. vaccination was associated with the preservation of Gag-specific central memory CD8 ϩ T cells in peripheral lymphoid tissue that were functionally capable of producing IFN-␥, and effector memory CD8 ϩ T cells that were capable of producing granzyme B after exposure to SIV (66,68). However, the influence of route of immunization on the generation of functionally active CD8 ϩ T cells, especially high-avidity CD8…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that i.m. vaccination was associated with the preservation of Gag-specific central memory CD8 ϩ T cells in peripheral lymphoid tissue that were functionally capable of producing IFN-␥, and effector memory CD8 ϩ T cells that were capable of producing granzyme B after exposure to SIV (66,68). However, the influence of route of immunization on the generation of functionally active CD8 ϩ T cells, especially high-avidity CD8…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of such cell types does not predict vaccine efficacy with consistency. Some studies have implicated a protective role of central memory (CM) T cells, although others have suggested a protective role for effector memory (EM) cells (6,16). These studies highlight the need to understand and discriminate among differences in CD8 T-cell responses generated by different vaccines; we have therefore compared vaccine-elicited cellular immune responses elicited by three different gene-based vaccine regimens through transcriptional profiling and the application of a technique that has allowed us to measure 96 gene-expression signals from single immune cells.…”
mentioning
confidence: 99%
“…The results of the current study clearly show that vaccine-induced epitope-specific CD8 ϩ T-lymphocyte clones expand and persist in the face of replicating virus. While we have not evaluated the functional integrity of these clonal T-lymphocyte populations in the present study, we have recently shown that prior vaccination protects the functional integrity of epitope-specific CD8 ϩ T-lymphocyte populations following a pathogenic-SHIV challenge (1).…”
Section: Discussionmentioning
confidence: 96%
“…However, generating such cell populations may ultimately prove challenging, as T-cell persistence in vivo is limited by many factors. Specifically, persistence is restricted by homeostatic mechanisms that limit T-lymphocyte division, clonal deletion of CD8 ϩ T lymphocytes through activationinduced cell death, and clonal exhaustion leading to loss of T-cell function, all of which have been described in the setting of persistent antigenic stimulation (1,5,13,18,20,23,24,38,43,50,55,60,62,65,67,69). HIV-1-specific CD8 ϩ T lymphocytes, in particular, can be highly activated during the primary immune response and are consequently especially prone to apoptosis (6,45).…”
mentioning
confidence: 99%